PLAG1‐rearrangement in a uterine leiomyosarcoma with myxoid stroma and heterologous differentiation. Issue 10 (8th July 2021) - Thiryayi, Sakinah A.; Turashvili, Gulisa; Latta, Eleanor K.; Swanson, David; Zhang, Lei; Antonescu, Cristina R.; Dickson, Brendan C.
Abstract: A variety of molecular alterations have been reported in uterine leiomyosarcomas, but most are considered nondiagnostic. There are, however, rare exceptions including PLAG1 rearrangement which has recently been identified in a subset of myxoid leiomyosarcomas. A 41‐year‐old woman presented with symptoms of a fibroid. She underwent a myomectomy which revealed a high‐grade uterine sarcoma with areas of myxoid stroma and heterologous elements. The tumor expressed desmin, smooth muscle actin, H‐caldesmon, and estrogen and progesterone receptors. RNA sequencing revealed a novel TRIM13‐PLAG1 fusion gene which was subsequently independently confirmed by fluorescence in situ hybridization. On further evaluation the patient was found to have multiple pulmonary metastases and died due to disease progression shortly after diagnosis. This report describes a novel fusion partner of PLAG1 in a uterine leiomyosarcoma with myxoid leiomyosarcoma and heterologous elements, thereby broadening the spectrum of morphologic and genetic findings within this rare group of neoplasms.